Stroke Severity Predicted by Aortic Atheroma Detected by Ultra-Fast and Cardiac-Gated Chest Tomography† - Lazzaro, Marc A.; Zaidat, Osama O.; Issa, Mohammad; Gilkeson, Robert C.; Sunshine, Jeffery L.; Tarr, Robert W.; Hakim, Shakir H.; Suarez, Jose I. (Frontiers in Neurology, 2011)
Background and Purpose: The presence of aortic atherosclerosis is an independent risk factor for secondary stroke. The present study was designed to have an initial exploration of the correlation between the load and extent of aortic atheroma (AA) and initial stroke severity or clinical outcome 3 months after stroke. Methods: Cardiac gated chest tomography (CGCT) was used to detect and measure AA in patients with acute ischemic stroke as shown by our group in prior prospective studies and this is part four sub-exploratory study of the same cohort. The National Institute of Health Stroke Scale (NIHSS) was used to assess the initial stroke severity, and the modified Rankin Scale (mRS) was used to assess 3-month outcome. Results: Thirty-two patients underwent CGCT for evaluation of aortic atheroma, and 21 were found to have AA. Aortic atheroma was more prevalent in patient with NIHSS > 6 (14/17 versus 7/15, p-value 0.03). Applying the multiple logistic regression and propensity score adjustment (using the propensity of having AA given the baseline features as covariates) showed a non-significant trend that AA is 3 times more likely to be associated with NIHSS > 6 (p=0.08, OR 3.08, 95%CI 0.94 to 13.52). There was no evidence of association of AA with 3-month functional outcome (mRS): 11/14 (78.6%) mRS >1 had AA, and 10/18 (55.5%) of those with mRS  1had AA (p=0.27). Conclusion: In our current study with limited sample number and exploratory nature, the presence of AA on CGCT with acute ischemic stroke patients may be associated with worse neurological deficit at presentation. There was no evidence of association with 3-month functional outcome using the modified Rankin Scale.